Civic education of children and youth in public organizations - N. Yu. Zhelnakova (Вестник Северо-Кавказского федерального университета)
Introduction. The topicality of improving civic education of children and youth is determined by special sociopedagogical conditions. In domestic educational practice, significant experience in civic education through public organizations has been accumulated.Goal. The study aims to specify the features of the influence of children and youth public organizations on civic education at different stages of the development of the country.Materials and methods. The study is based on the analysis of documents regulating the activities of children and youth organizations and associations, and the works of leading specialists.Results and discussion. It has been established that civic education in children communities and organizations contributes to the formation of experience of social interaction, independence, initiative, and leadership qualities. Priorities in the work of children and youth organizations changed during the 19th-21st centuries; differences in work and results make it possible to identify productivity factors in civic education.Conclusion. Based on the results of the study, we can conclude that with a clearly defined social demand for the formation and manifestation of civic qualities, high results can be obtained in children and youth public organizations.